Rising powers' quest for increased legitimacy through IOs in an era of loose multilateralism - PARLAR DAL, EMEL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
This paper critically assesses the (de)legitimation strategies used by rising powers against existing formal and informal International Organizations (IOs), especially the G7/8, the World Bank and the International Monetary Fund (IMF). In doing so, it first analyzes how legitimacy relates to multilateralism and vice versa. Then, it examines why legitimacy matters to rising powers the two main (de)legitimation strategies-regime shift and competitive regime creation-used by rising powers when they contest the legitimacy of the existing IOs. Finally, it uses the cases of the G20 and the Asian Infrastructure Investment Bank (AIIB) to highlight the strengths and limits of regime shift and competitive regime creation strategies. This paper argues that rising powers' quest for enhanced legitimacy by means of joining alternative existing institutions (G20) or creating new institutions (AIIB) seems to have produced limited results because, like the status-quo institutions, the G20 and AIIB also suffer from legitimacy deficit.
Keywords: Legitimacy; rising powers; multilateralism; G20; AIIB; International Organizations (IOs); INFRASTRUCTURE INVESTMENT BANK; CIVIL-SOCIETY; G20; GOVERNANCE; CHINA; ENGAGEMENT; EVOLUTION; SEARCH; WORLD